Adaptive RSK‐EphA2‐GPRC5A signaling switch triggers chemotherapy resistance in ovarian cancer. Issue 4 (2nd March 2020) - Moyano‐Galceran, Lidia; Pietilä, Elina A; Turunen, S Pauliina; Corvigno, Sara; Hjerpe, Elisabet; Bulanova, Daria; Joneborg, Ulrika; Alkasalias, Twana; Miki, Yuichiro; Yashiro, Masakazu; Chernenko, Anastasiya; Jukonen, Joonas; et al.
Abstract: Metastatic cancers commonly activate adaptive chemotherapy resistance, attributed to both microenvironment‐dependent phenotypic plasticity and genetic characteristics of cancer cells. However, the contribution of chemotherapy itself to the non‐genetic resistance mechanisms was long neglected. Using high‐grade serous ovarian cancer (HGSC) patient material and cell lines, we describe here an unexpectedly robust cisplatin and carboplatin chemotherapy‐induced ERK1/2‐RSK1/2‐EphA2‐GPRC5A signaling switch associated with cancer cell intrinsic and acquired chemoresistance. Mechanistically, pharmacological inhibition or knockdown of RSK1/2 prevented oncogenic EphA2‐S897 phosphorylation and EphA2‐GPRC5A co‐regulation, thereby facilitating a signaling shift to the canonical tumor‐suppressive tyrosine phosphorylation and consequent downregulation of EphA2. In combination with platinum, RSK inhibitors effectively sensitized even the most platinum‐resistant EphA2 high, GPRC5A high cells to the therapy‐induced apoptosis. In HGSC patient tumors, this orphan receptor GPRC5A was expressed exclusively in cancer cells and associated with chemotherapy resistance and poor survival. Our results reveal a kinase signaling pathway uniquely activated by platinum to elicit adaptive resistance. They further identify GPRC5A as a marker for abysmal HGSC outcome and putative vulnerability of the chemo‐resistant cells to RSK1/2‐EphA2‐pS897 pathway inhibition. Synopsis: Platinum chemotherapy induces RSK1/2‐EphA2‐GPRC5A oncogenic signaling switch associated to intrinsic and acquired resistance. This study identifies GPRC5A as a marker for poor therapy response and vulnerability of the resistant cells to RSK1/2‐EphA2‐pS897 pathway inhibition in ovarian cancer. The oncogenic switch is mediated by platinum‐activated ERK1/2‐RSK1/2 pathway coupled with co‐localization of EphA2 and the EphA2‐interacting orphan receptor GPRC5A. RSK inhibition impairs, through EphA2‐pY588 activation and consequent EphA2 downregulation, the platinum‐induced resistance‐associated GPRC5A‐EphA2‐pS897 co‐regulation, thus sensitizing HGSC cell to platinum. GPRC5A expression is associated with HGSC cell sensitivity to RSKi‐platinum combination treatment ex vivo . In human HGSC tumors, high GPRC5A levels are correlated with poor treatment response, as well as adverse overall and progression‐free patient survival. Combined EphA2‐GPRC5A expression predict shorter progression‐free survival. Abstract : Platinum chemotherapy induces RSK1/2‐EphA2‐GPRC5A oncogenic signaling switch associated to intrinsic and acquired resistance. This study identifies GPRC5A as a marker for poor therapy response and vulnerability of the resistant cells to RSK1/2‐EphA2‐pS897 pathway inhibition in ovarian cancer.